Using Interest Approaches in Instructional Design and Delivery - Brianna N. Shanholtzer; Andrew Thoron; J. C. Bunch; Blake C. Colclasure (EDIS)
Most educators know that it can be challenging to get students motivated to learn at the start of a lesson. The importance of student motivation, academic desire, and engagement is well noted as these factors have been directly linked to students’ academic achievement. An interest approach uses a brief activity to stimulate students’ situational interest toward a topic. Although situational interest is typically held by the learner for a short duration, establishing situational interest at the start of the lesson maximizes students’ engagement, motivation, and attentiveness toward the lesson’s topic and student learning objectives. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication describes components of interest approaches and techniques for integrating them into a lesson, and provides real-world examples. Written by Brianna N. Shanholtzer, Andrew C. Thoron, J. C. Bunch, and Blake C. Colclasure. http://edis.ifas.ufl.edu/wc334